Peran Stres Kerja sebagai Mediasi pada Pengaruh Beban Kerja Terhadap Kinerja Karyawan - Muhamad Ekhsan; Achmad Masruri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The progress of a company cannot be separated from the existence and influence of the human resources in it. Human resources are the company's main engine in carrying out all activities to achieve goals. In a company, people are one of the most important elements. Without the role of humans, the company will not run. Because humans are the factors that drive and determine the running of a company. One of the factors that influence the success of an organization is the performance of its employees. Efforts to improve employee performance are to pay attention to workload and work stress.This study aims to determine and analyze the effect of workload on employee performance mediated by work stress. This research was conducted at PT SII, with a research sample of 97 employees. The sampling method used the slovin formula with a margin of error of 5% on a population of 128 employees. Data collection was carried out by distributing questionnaires via google form to the production department of PT SII. The analysis method uses smartPLS 3.0. The results of this study indicate indirectly that workload has a positive but not significant effect on employee performance. Workload has a positive and significant effect on work stress and work stress has no positive and significant effect on employee performance at PT. SII. In this study the role of work stress could not mediate the effect of workload on employee performance at PT. SII.